2022
DOI: 10.1038/s41598-022-22088-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of stability and unfolding cooperativity in hPGK1 upon gradual structural perturbation of its N-terminal domain hydrophobic core

Abstract: Phosphoglycerate kinase has been a model for the stability, folding cooperativity and catalysis of a two-domain protein. The human isoform 1 (hPGK1) is associated with cancer development and rare genetic diseases that affect several of its features. To investigate how mutations affect hPGK1 folding landscape and interaction networks, we have introduced mutations at a buried site in the N-terminal domain (F25 mutants) that either created cavities (F25L, F25V, F25A), enhanced conformational entropy (F25G) or int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Applying this formula will provide m 1 , m 2 , and m 3 in addition to the free energy differences between the native form and the intermediate, and unfolded states. T is the experimental temperature (298.15 K), and R is the ideal gas constant ( Pacheco-García et al., 2022 ). X N , X 1 , and X U are the mole fractions of the proteins in their native, intermediate, and unfolded states, respectively, and Q is the partition function.…”
Section: Methodsmentioning
confidence: 99%
“…Applying this formula will provide m 1 , m 2 , and m 3 in addition to the free energy differences between the native form and the intermediate, and unfolded states. T is the experimental temperature (298.15 K), and R is the ideal gas constant ( Pacheco-García et al., 2022 ). X N , X 1 , and X U are the mole fractions of the proteins in their native, intermediate, and unfolded states, respectively, and Q is the partition function.…”
Section: Methodsmentioning
confidence: 99%
“…m N and m U represent the slopes of the native and unfolded state baselines, while m denaturants describe the unfolding cooperativity. R is the ideal gas constant, and T is the experimental temperature (298.15 K) (Pacheco-García et al, 2022). This model provides a simplified approach for comparing the cooperativity of reversible chemical unfolding in A. lakoocha peroxidase.…”
Section: Methodsmentioning
confidence: 99%
“…It is still an open question whether the changes in protein geometry are significant after modification [29,30]. For instance, Juan Luis Pacheco-García et al note the loss of stability in human isoform 1 caused by a disruption of the hydrophobic core in the N-terminal domain due to amino acid substitutions or post-translational modification [31]. There are also studies that indicate minor structural changes resulting from protein modifications [30,[32][33][34] Fuxiao Xin and Predrag Radivojac showed that the proportion of significant conformational changes (RMSD>2 Å) after glycosylation is estimated to be only 7%, and after phosphorylation, it is approximately 13% [30].…”
Section: Introductionmentioning
confidence: 99%